2023
DOI: 10.1139/cjas-2023-0001
|View full text |Cite
|
Sign up to set email alerts
|

A survey of broiler breast meat quality in the retail market of Quebec

Abstract: In this study, 206 breast fillets were purchased from grocery stores in the province of Quebec and evaluated for the presence of different quality defects. Of these fillets, 48.5% showed breast muscle myopathies (BMM), 19.4% showed pale, soft and exudative (PSE), and 6.8% showed dark, firm and dry (DFD) attributes. BMM were equally present (P > 0.05) in fillets of economical, commercial, and high-quality brands while PSE-Like fillets were more present in economical brands (P < 0.0001). The combined effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The increased production of ROS in myopathic muscles due to hypoxia results in a concomitant increase of lipid peroxidation, as well as protein and DNA oxidation products. The thiobarbituric acid–reactive substances (TBA-RS) index is a widely used method to assay secondary products of lipid peroxidation ( Sammari et al, 2023 ). Using this method, multiple studies have reported significantly increased levels of malondialdehyde (MDA) in WS- ( Carvalho et al, 2021 ; Pereira et al, 2022 ) and WB-affected muscles, indicating elevated levels of lipid peroxidation ( Soglia et al, 2019 ; Pan et al, 2021 ; Li et al, 2022 ).…”
Section: Hypoxia Alters Mitochondrial Morphology Dynamics and Functio...mentioning
confidence: 99%
“…The increased production of ROS in myopathic muscles due to hypoxia results in a concomitant increase of lipid peroxidation, as well as protein and DNA oxidation products. The thiobarbituric acid–reactive substances (TBA-RS) index is a widely used method to assay secondary products of lipid peroxidation ( Sammari et al, 2023 ). Using this method, multiple studies have reported significantly increased levels of malondialdehyde (MDA) in WS- ( Carvalho et al, 2021 ; Pereira et al, 2022 ) and WB-affected muscles, indicating elevated levels of lipid peroxidation ( Soglia et al, 2019 ; Pan et al, 2021 ; Li et al, 2022 ).…”
Section: Hypoxia Alters Mitochondrial Morphology Dynamics and Functio...mentioning
confidence: 99%